A method to convert MRI images of temperature change into images of absolute temperature in solid tumours. (September 2013) - Davis, Ryan M.; Viglianti, Benjamin L.; Yarmolenko, Pavel; Park, Ji-Young; Stauffer, Paul; Needham, David; Dewhirst, Mark W.
Abstract Purpose: During hyperthermia (HT), the therapeutic response of tumours varies substantially within the target temperature range (39–43 °C). Current thermometry methods are either invasive or measure only temperature change, which limits the ability to study tissue responses to HT. This study combines manganese-containing low temperature sensitive liposomes (Mn-LTSL) with proton resonance frequency shift (PRFS) thermometry to measure absolute temperature in tumours with high spatial and temporal resolution using MRI. Methods: Liposomes were loaded with 300 mM MnSO4. The phase transition temperature (Tm) of Mn-LTSL samples was measured by differential scanning calorimetry (DSC). The release of manganese from Mn-LTSL in saline was characterised with inductively coupled plasma atomic emission spectroscopy. A 2T GE small animal scanner was used to acquire dynamic T1-weighted images and temperature change images of Mn-LTSL in saline phantoms and fibrosarcoma-bearing Fisher-344 rats receiving hyperthermia after Mn-LTSL injection. Results: The Tm of Mn-LTSL in rat blood was 42.9 ± 0.2 °C (DSC). For Mn-LTSL samples (0.06 mM–0.5 mM Mn2+ in saline) heated monotonically from 30 °C to 50 °C, a peak in the rate of MRI signal enhancement occurred at 43.1° ± 0.3 °C. The same peak in signal enhancement rate was observed during heating of fibrosarcoma tumours (N = 3) after injection of Mn-LTSL, and the peak was used to convert temperature change images into absolute temperature. Accuracies of calibrated temperature measurements were in the range 0.9–1.8 °C. Conclusion: The release of Mn2+ from Mn-LTSL affects the rate of MR signal enhancement which enables conversion of MRI-based temperature change images to absolute temperature.